Marine power plant - Yang, Zongming (Elsevier, 2021)
This book describes the history and development of marine power plant. Problems of arrangement, general construction and parameters of marine power plants of all types are considered. It also introduces different characteristics of each type of marine power plant, matching characteristic for diesel propulsion. The book gives a clear idea about different marine power engines, including working principle, structure and application. Readers will understand easily the power system for ships since there are a lot of illustrations and instructions for each of the equipment. This book is useful for students majoring in “marine engineering”, “energy and power engineering” and other related majors. It is also useful for operators of marine institution for learning main design and operation of ship plants.